КОРЕСПОНДЕНЦИЈАТА (ЕПИСТОЛАРИЈАТА) НА МАКЕДОНСКИТЕ ЖЕНИ ВО XIX ВЕК - Славчо Ковилоски (Универзитет „Гоце Делчев“, Филолошки факултет, Штип, 2017)
The Macedonian XIX century abounds in a huge collection of postcards and letters, written on various occasions and dealing with various issues. It is in the correspondence where one finds the most numerous examples of female authorship in the nineteenth century. In the letters, the creative activity of women's authorship is at its peak. Through them we can see the everyday life of the authors. As very important for the Macedonian women's correspondence from this period, we single out the letters of Mitra Miladinova, Efrosina Dimitrova Robeva, Evtimia P. Bozhkova, Zachariya Naumcheva, Kotsa K. Kemenzhieva etc.